CNS metastasis secondary to malignant-mixed Müllerian tumor: case report and review of therapeutics. (October 2017) - Healy, Vincent; O'Halloran, Philip; O'Brien, Sorca; Beausang, Alan; Caird, John
This paper reviews CNS involvement secondary to malignant-mixed Müllerian tumor or uterine carcinosarcoma, a rare aggressive biphasic Müllerian tumor. We report a cerebellar metastasis with epithelial and mesenchymal components, demonstrating heterologous rhabdomyogenic and chondroblastic differentiation. The patient had undergone total abdominal hysterectomy and bilateral salpingo-oophorectomy for palliation of symptomatic chemotherapy-resistant node-positive disease. CNS involvement is rare, and prognostically poor, and suggestively poorer in predominantly sarcomatous metastases. Multimodal therapy is indicated; in solitary metastases, surgical resection or stereotactic radiosurgery is included, followed by whole brain radiotherapy. In unresectable brain metastases, stereotactic radiosurgery and whole brain radiotherapy warrant consideration in up to 2–3 metastases. In multiple metastases, palliative steroid therapy or cranial irradiation may be considered. Combination or platinum-based chemotherapy (i.e., ifosfamide-paclitaxel or carboplatin-paclitaxel) is indicated in all stages, with a role in both disease cure and control-directed management. Targeted therapeutics have thus far not demonstrated significant clinical efficacy.